2020
DOI: 10.1177/0883911519894667
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer decorated herbal cell compatible scaffolds for bone tissue engineering: A synergistic effect of graphene oxide andCissus quadrangularis

Abstract: Among various bone regenerative and repair methods, use of osteoinductive scaffold as bone grafts/substitute has gained wide importance worldwide. To develop such osteoinductive scaffold that is more natural and which spontaneously stimulates osteoblast formation without any differentiation media, we prepared electrospun poly ε-caprolactone scaffold which is further modified by means of layer-by-layer method using Cissus quadrangularis callus culture extract and graphene oxide (PCL-GO-CQ). The modified PCL-GO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…[17] Moreover, many researchers showed the positive role of graphite derivatives on the bioactivity, biocompatibility, and biodegradability of PCL-based scaffolds. [18,19] For instance, Wang et.al fabricated PCL/graphene (G) composites scaffolds and characterized them. [20] The study demonstrated that the PCL/G scaffolds cause an appropriate level of an immune response, indicating a high potential for in vivo applications.…”
mentioning
confidence: 99%
“…[17] Moreover, many researchers showed the positive role of graphite derivatives on the bioactivity, biocompatibility, and biodegradability of PCL-based scaffolds. [18,19] For instance, Wang et.al fabricated PCL/graphene (G) composites scaffolds and characterized them. [20] The study demonstrated that the PCL/G scaffolds cause an appropriate level of an immune response, indicating a high potential for in vivo applications.…”
mentioning
confidence: 99%
“…Due to its high calcium and phosphorus content, CQ stimulates metabolism and increases the absorption of minerals. Therefore, it promotes the proliferation and osteogenic differentiation of bone marrow-derived MSCs (mesenchymal stem cells) [195]. Other researchers are also looking for new solutions from more herbal medicines, such as Plastrum Testudinis [185] for the treatment of disc inflammation, Elaeagnus angustifolia (EA) [52] for the treatment of rheumatoid arthritis and osteoarthritis, Clove [109] and Ziziphus jujuba [21] for the treatment of periodontal disease, and Amla oil [56] with rich antioxidant and mineral components.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Through the provision of new replacements with advantageous multifunctional properties, this creative technique shows potential for enhancing bone tissue engineering. An osteoinductive scaffold designed by Kashte et al [188] used a naturally occurring bioactive substance to stimulate the production of osteoblasts. PCL-GO-CQ is the outcome of the layer-by-layer construction of this scaffold utilizing electrospun PCL, Cissus quadrangularis extract, and GO.…”
Section: Bone Regeneration Systemsmentioning
confidence: 99%